Pembuatan Biofuel Dari Minyak Goreng Bekas Melalui Proses Catalytic Cracking Dengan Katalis Fly Ash - Hazzamy, M Asyraf; Zahrina, Ida; Yelmida, Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Petroleum is a fossil fuel that can not be renewed but dwindling availability. Biofuel is a renewable alternative energy that can replace petroleum. The manufacture of biofuels by using catalytic cracking feedstock used cooking oil. Cooking oil is a waste product of the food industry. Dangerous if used cooking oil because it contains carcinogens and when discharged into the environment causing pollution. Oleic acid and palmitic acid contained in the used cooking oil is high enough to be able to be converted into biofuel. Variations used are temperature process (380 0C, 400 0C, 420 0C) and weight of fly ash 5%, 7% and 9% of the weight of used cooking oil. This study aims to produce a maximum yield of biofuel from used cooking oil by catalytic cracking catalyst silica from fly ash oil. Results were analyzed by the method viskosimetri cracking. Density stands at cracking results from 0.7727 to 0.7930 g / ml. Best yield obtained was 31.72% at 420 0C and 9% by weight of fly ash. Â Keyword : Biofuel, catalytic cracking, fly ash, wasted cooking oil